Evaluating social (pragmatic) communication disorder. (25th July 2017) - Mandy, William; Wang, Adele; Lee, Irene; Skuse, David
Abstract : Background: Social (pragmatic) communication disorder (SPCD) is a new diagnosis introduced by DSM‐5, characterised by problems with verbal and nonverbal social communication. It is currently unclear whether SPCD is a valid diagnostic category, because little is known about the characteristics of those who meet its criteria. We sought to identify and describe cases of SPCD, to contribute to debates about its validity. We investigated whether the symptoms of SPCD cluster together to form a coherent syndrome that is distinct from autism spectrum disorder (ASD) in terms of its core and associated features. Methods: Participants were young people ( N = 1, 081, age range = 4–18 years) who had attended a specialist social communication disorders clinic for children with fluent language and normal‐range intelligence. Standardised parent‐report data were collected using the Developmental, Dimensional and Diagnostic Interview (3Di), Child Communication Checklist (CCC) and Strengths and Difficulties Questionnaire (SDQ). An algorithm was designed using 3Di and CCC items to implement DSM‐5 SPCD criteria. Results: Eighty‐eight young people met our criteria for SPCD, with 801 meeting DSM‐5 ASD criteria and the remaining 192 having neither SPCD nor ASD ('clinical comparison group'). The core symptoms of SPCD co‐occurred to a moderate degree (average interitem correlation = .22). SPCD cases had autistic social difficulties that were intermediate between ASD and the clinical comparison group. SPCD was associated with high rates of nonautistic psychopathology, with 63.5% scoring in the abnormal range of the SDQ's Total Problems scale. Conclusions: We did not find evidence that SPCD is qualitatively distinct from ASD. Rather, it appears to lie on the borderlands of the autism spectrum, describing those with autistic traits that fall just below the threshold for an ASD diagnosis. SPCD may have clinical utility for identifying people with autistic traits that are insufficiently severe for ASD diagnosis, but who nevertheless require support.